Strangulated Morgagni’s Hernia: A Rare Diagnosis and Management - Malav Modi; Amit Kumar Dey; Ajay Mate; Samir Rege (Case Reports in Surgery)
Morgagni hernia is a rare type of congenital diaphragmatic hernia. It accounts for only 3% of all diaphragmatic hernias. The defect is small and hernia being asymptomatic in the majority presents late in adulthood. Obstruction or incarceration in Morgagni hernia is uncommon. We report a rare occurrence of strangulated Morgagni hernia. A 40-year-old gentleman presented to our emergency department with features of intestinal obstruction. Computed tomography of the chest and abdomen showed a strangulated right Morgagni hernia. An exploratory laparotomy was performed with resection of the ischemic bowel segment with anastomosis and a primary repair of the diaphragmatic defect. Postoperative recovery was uneventful and asymptomatic at follow-up.